Strategi Bertutur dalam Tindak Tutur Mengkritik pada Series “Layangan Putus” - Rani Wulandari; Ngusman Abdul Manaf (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This study examines speech strategies used in criticism speech acts in the Layangan Putus series. The research aims to describe the types of speech strategies and the speech situation contexts underlying their use. This study employs a descriptive qualitative method. The data consist of utterances containing criticism speech acts in the Layangan Putus series. Data were collected through observation and note-taking techniques, and analyzed using pragmatic analysis based on Brown and Levinson’s politeness theory. The results show that criticism in the series is realized through four speech strategies, namely speaking directly without hedging, speaking directly with positive politeness, speaking directly with negative politeness, and speaking indirectly. The most dominant strategy is speaking directly without hedging, especially through imperative sentence forms and explicit performatives. The use of speech strategies is influenced by the speech situation context, particularly power relations and the level of familiarity between speaker and hearer. In general, the findings indicate that criticism in the series is not only used to express negative evaluation but also reflects the speaker’s effort to maintain social relations and politeness in interaction.